2021
DOI: 10.3389/fpls.2021.808899
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite and Transcriptome Profiling Analysis Revealed That Melatonin Positively Regulates Floral Scent Production in Hedychium coronarium

Abstract: Melatonin is a pleiotropic molecule that regulates a variety of developmental processes. Floral volatiles are important features of flowers that facilitate flower–visitor interactions by attracting pollinators, structure flower–visitor communities, and play defensive roles against plant and flower antagonists. Aside from their role in plants, floral volatiles are an essential ingredient in cosmetics, perfumes, pharmaceuticals, and flavorings. Herein, integrated metabolomic and transcriptomic approaches were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Similar results were reported in the floral volatile profile of numerous species, including H . coronarium (Abbas, Zhou, et al, 2021; Zhou et al, 2021). To effectively screen various metabolites between different groups, a combination approach of OPLS‐DA and VIP analysis was applied (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar results were reported in the floral volatile profile of numerous species, including H . coronarium (Abbas, Zhou, et al, 2021; Zhou et al, 2021). To effectively screen various metabolites between different groups, a combination approach of OPLS‐DA and VIP analysis was applied (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, gene‐to‐metabolite study in H . coronarium revealed that MYB/bHLH were the key transcription factors interconnected with multiple nodes of important volatile components (Abbas, Zhou, et al, 2021). Likewise, similar findings were observed in Osmanthus fragrans (Zhou et al, 2017), Freesia x hybrida (Gao et al, 2018), Camellia oleifera (Yang et al, 2022), and Chrysanthemum dichrum (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Ashraf et al (2017) and Ashraf and Tang (2017) reported the deterioration in rice grain quality attributes under heavy metal toxicity. It has been demonstrated that exogenous hormone application improves plant fitness via maximizing the transcriptional level of related biosynthesis pathway genes in plants ( Abbas et al, 2021a , b ). Mineral elements contents were increased in treatments with applied MeJa, while under Cd stressed treatments, mineral elements contents reduced greatly.…”
Section: Discussionmentioning
confidence: 99%